제2-3기 주상골 불유합 진행성 붕괴의 관혈적 무두나사 고정 및 자가 장골 이식술 치료 - 강호정(Ho-Jung Kang); 고일현(Il-Hyun Koh); 최윤락 (Yun-Rak Choi); 김지섭(Ji-Sub Kim); 박영창(Young-Chang Park) (The journal of the Korean Orthopaedic Association, 2016)
목적: 제2-3기 주상골 불유합 진행성 붕괴의 환자에서 무두나사를 이용한 관혈적 고정술과 자가 장골 이식술의 치료 결과를 알아보고자 하였다. 대상 및 방법: 2010년 6월부터 2013년 6월까지 강남세브란스병원에서 제2-3기 주상골 불유합 진행성 붕괴의 환자 중 관혈적 무두나사 고정술 및 자가 장골 이식술을 시행한 10명의 환자를 후향적으로 분석하였다. 영상적 결과는 골유합, 주상월상각 및 측면 주상골내각으로 평가하였고 임상적 결과는 관절운동 범위, 통증, 악력, Mayo wrist score, Maudsley 평가법으로 평가하였다. 결과: 모든 환자에서 유합 소견을 보였다. 최종 추시상 관절면의 경화 및 낭성 병변, 골 감소 병변의 정상화 및 관절면이 매끄러워지는 소견을 보였다. 술 전과 비교하여 술 후 통증은 감소하였으며, 약력 및 Mayo wrist score는 유의미하게 호전되었다. 주상월상각 및측면 주상골내각은 수술 후 감소하였으나 유의미하지는 않았다. Maudsley 평가법은 우수 4예, 양호 4예, 보통 2예의 결과를 보였다. 결론: 제2-3기 주상골 불유합 진행성 붕괴에서 주상골의 안정성 회복이 중요하며 관혈적 무두나사 고정술과 자가 장골 이식술로 만족할 만한 임상적, 방사선적 결과를 얻었다. 이에 추천할 만한 치료로 생각된다 Purpose: The purpose of this study is to investigate the outcome of open reduction and internal fixation with a headless screw and auto iliac bone graft for patients of scaphoid nonunion advanced collapse (SNAC) stage II and III. Materials and Methods: A retrospective analysis was conducted for 10 patients diagnosed with stage II or III SNAC, and consequently treated with open reduction and internal fixation with a headless screw and auto iliac bone graft with or without radial styloidectomy between 2010 and 2013. Radiographic results were evaluated by bone union, the scapholunate angle and lateral intrascaphoid angle. Clinical results were evaluated by range of motion, pain, grip strength, Mayo wrist score, and assessment of Maudsley. Results: All patients showed union after the operation. Final follow-up X-rays show smoothening of the articular surface with improvement of sclerotic lesions of the articular surface, cystic lesions and osteopenic lesions. Pain decreased after the operation compared with preoperative status, grip strength and Mayo wrist score showed significant improvement. Scapholunate angle and lateral intrascaphoid angle decreased after the operation, but it was not significant. According to assessment of Maudsley, among 10 cases, there were 4 excellent cases, 4 good cases and 2 fair cases. Conclusion: Restoration of stability of scaphoid is important to SNAC stage II and III, open reduction and internal fixation with a headless screw and auto iliac bone graft shows satisfactory clinical and radiologic outcomes. Thus it is considered a recommendable operation. KCI Citation Count: 0